Benefits of pruning in custard apple - Choudhary, Kalpana; Meena, Nirmal Kumar (Indian Horticulture, 2020)
Pruning plays crucial role in rejuvenating senile and old orchard as well as to increase fruiting branches. Pruned tree yielded many fold higher number of fruits with enhanced quality. For getting regular high yield custard apple growers are recommended to do pruning at the intensity of 30% which was found most suitable in Maharashtra area.